2018
DOI: 10.1016/j.neuroimage.2017.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of childhood neglect and abuse during sensitive exposure periods on male and female hippocampus

Abstract: The hippocampus is a highly stress susceptible structure and hippocampal abnormalities have been reported in a host of psychiatric disorders including major depression and post-traumatic stress disorder (PTSD). The hippocampus appears to be particularly susceptible to early life stress with a graded reduction in volume based on number of types (multiplicity) or severity of maltreatment. We assessed whether the most important predictors of adult hippocampal volume were multiplicity, severity or duration of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 53 publications
8
97
1
4
Order By: Relevance
“…This argumentation is in line with the present investigation, as our sample included adults with experience of prolonged and severe maltreatment. With regard to the hippocampus, a number of studies found reduced hippocampal volume in adult samples 23 , while studies in children or adolescents exposed to neglect have not typically observed changes in hippocampus volume 16 . As observed in the amygdala, it is hypothesized that there may be a silent period between exposure to maltreatment and discernible neurobiological differences, with observable cross sectional differences becoming fully discernible in later life 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This argumentation is in line with the present investigation, as our sample included adults with experience of prolonged and severe maltreatment. With regard to the hippocampus, a number of studies found reduced hippocampal volume in adult samples 23 , while studies in children or adolescents exposed to neglect have not typically observed changes in hippocampus volume 16 . As observed in the amygdala, it is hypothesized that there may be a silent period between exposure to maltreatment and discernible neurobiological differences, with observable cross sectional differences becoming fully discernible in later life 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Early life social adversity results in abnormalities in BDNF methylation and mRNA expression, including in the hippocampus and amygdala (Miskolczi et al, 2019). Also, there are sex differences in BDNF expression (Bath, Schilit, & Lee, 2013) and sensitive periods, and associated effects on amygdala and hippocampal volume (Pechtel, Lyons-Ruth, Anderson, & Teicher, 2014;Teicher et al, 2018). In their model, Miskolczi et al (2019) argue that sex (along with genetic factors) influence brain developmental curves, that the trajectory of these developmental curves are region-specific and furthermore determine the timing of sensitive periods for each region, and that depending on the timing of the early life adversity, separable brain regions might undergo disturbed development, resulting in aberrant maturation and increased risk of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…See references for details. [160][161][162] The first study was conducted at McLean Hospital's Developmental Biopsychiatry Research Program (PI: Martin Teicher, MD, PhD) entitled "Sensitive Periods, Brain Development and Depression Study". The group aimed to test the hypothesis that there are discrete sensitive periods when exposure to abuse or loss is maximally associated with risk for developing psychiatric disorders, specifically major depression and that risk for developing depression coincided with exposure to abuse during sensitive periods of hippocampal and prefrontal cortex vulnerability.…”
Section: Mclean Trauma Sample (Teic; Supplementary Table 1 #39)mentioning
confidence: 99%